Modelling and validation of bacterial O-antigen conformations: ring puckering in Shigella flexneri 7a and 7b O-antigens as a case study - Timol, Zaheer (Department of Computer Science, 2025)
This work forms part of a larger project investigating the conformation and dynamics of Shigella flexneri O-antigens. S. flexneri is a leading cause of diarrhoeal related diseases, especially in Sub-Saharan Africa and Southeast Asia. There are over 30 S. flexneri serotypes and, with the exception of serotype 6, all share a common O-antigen backbone (serotype Y), with variations in glucosylation, phosphorylation, and O-acetylation. O-antigens are carbohydrate polymers on the outer membrane of gram-negative bacteria. In S. flexneri, O-antigens are a primary antigenic component and are a target for conjugate vaccines currently in development. Analysis of O-antigen conformation for different S. flexneri serotypes may inform the vaccine development process. However, determining molecular conformation experimentally is challenging. Systematic molecular modelling protocols have proven useful in elucidating conformations of polysaccharide antigens, especially when experimental methods, such as nuclear magnetic resonance, are used for verification of modelling results. Here we use a combination of molecular modelling and 1H nuclear magnetic resonance spectroscopy experiments to probe the O-antigen conformations of S. flexneri 7a and 7b. Simulations of six repeating units of both O-antigens show that they are highly flexible, similar to the S. flexneri Y O-antigen. However, we found frequent puckering of the β-D-GlcpNAc ring away from the canonical 4C1 conformer, which has not been previously observed in studies of Shigella or other bacterial O-antigens. To provide further insight, molecular dynamics and metadynamics simulations of a range of 3,4-disubstituted β-D-GlcNAc trisaccharides with two carbohydrate force fields (CHARMM36 and GLYCAM06) were performed. The simulations reveal that 3,4-α-linked β-D-GlcpNAc puckers to a similar extent as the S. flexneri 7a and 7b O-antigens. Moreover, for both force fields the range of β-D-GlcNAc puckering is dependant on the anomeric configuration of both the 3- and 4- linkage, with non-4C1 conformations dominant in 3,4-α-linked β-D-GlcpNAc trisaccharides. 1H nuclear Overhauser effect spectroscopy experiments were used to calculate 1H-1H distances in S. flexneri 7a and 7b O-antigens. These experimentally derived distances match those calculated from the repeating unit simulations when a mix of 4C1 and boat/skew states of β-DGlcpNAc are considered at a ratio of 85:15. The results also suggest that puckering of β-DGlcpNAc does occur in S. flexneri 7a and 7b O-antigens but that it may be over represented in the simulations. Two general observations can be drawn from this study: (1) the 3,4-disubstitution of β-DGlcpNAc with two bulky substituents leads to the ring puckering out of the 4C1 conformer; and (2) the conformation and dynamic behaviour of β-D-GlcpNAc puckering is not accurately modelled by current methods, identifying the need for further enhancements to existing carbohydrate force fields.